Pathos as Narrative Glue: Marnie the Novel, Film, and Opera (University of Bucharest Review. Literary and Cultural Studies Series, 2025)
This article looks at several ways in which personal trauma is the source of pathos in the etymological sense of suffering and affliction, engendering social failure in Winston Graham’s novel Marnie. Likewise, the study strives to demonstrate that both the literary original and its cinematic and operatic remediations are sparked into emotional cohesion by the narrative glue of pathos. From the perspective of both psychoanalysis and adaptation studies, this article reaches the conclusion that the open ending of the three versions also involves the reader/spectator in the process of narration – as Aristotle discovered in anticipation of Jauss’s reception theory – and thus leaves it to them to decide whether healing from pathos can ever be reached by the protagonist